KONVERGENSI ANTARA RESOURCE MOBILIZATIONTHEORY DAN IDENTITYORIENTED THEORYDALAM STUDI GERAKAN SOSIAL BARU - Oman Sukmana (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
In the study of New Social Movements (NSM), there are two dominanttheories that are each conflicting, namely the Resource MobilizationTheory (RMT) and the Identity-Oriented Theory (IOT).RMTwas born and developed in the U.S. viewing that the dynamics ofsocial movements tend to involve the dimensions of rationality, whileIOT born and developed in Europe who believe that the dynamicsof social movements tend to involve the dimensions of emotionality(emotive nature).Singh said that although the RMT and IOT bothhave very sharp differences, but these two theoretical perspectivesdoes not mean can not be integrated in explaining the phenomenonof social movements and collective action.This paper attempts to meetthe expectations of Singh for converging these two theories . From theresult of the convergence between RMT and IOT generate perspectivethere are at least 8 determinant factor in analyzing the New SocialMovements, namely: (1) social movement organizations, (2) Leadersand leadership, (3) Resources and resource mobilization, (4) Networkand participation, and (5) opportunities and community capacity toconduct social movements, (6) collective identity,(7) Solidarity, and(8) Commitment.